Defining the quality of urban life: Which factors should be considered? - Eva Psatha; Alex Deffner; Yannis Psycharis (European Regional Science Association (ERSA), 2011)
In 2010 the World Health Organisation dedicated the Word Health Day to urbanization and health, highlighting the impacts of urban living on physical and mental health. This is because it is increasingly acknowledged that cities face various problems that undermine the quality of urban life, e.g.social inequalities, urban crime, poor environment, and traffic congestion. Despite this fact, cities continue to play a vital role in development, as they offer higher education, specialized services and jobs. When it comes to an assessment of the living conditions and well-being in cities, economic indices have failed to capture the aforementioned contradiction of urban life. A concept able to monitor the multidimensional nature of cities seems to be the "quality of urban life" (QOUL). The multidimensionality of the QOUL concept reflects the variety of the examined dimensions, but also the range of the different uses of the term. Many different approaches of this concept can be found not only between papers of different disciplines (health sciences, social sciences or planning), but also in the context of the same scientific field. Thus, although there has recently been a remarkable number of comparative studies and papers concerning the evaluation of QOUL in different cities, the factors taken into account are far from being standard. In part, this is because the constituents of the QOUL depend on rather subjective factors, such as culture and tradition in the examined places. However, for a given place and a specific time period there can be an agreement concerning the determinants of QOUL. This will allow for relative research to be comparable and better interpretable. This paper starts with an analysis of the standard approaches of the QOUL concept as they can be found in the relative scientific literature. It continues with the analysis of QOUL determinants in societies, focusing in cities. The criteria taken into account for the measurement of the QOUL in the evaluation of cities and the city rankings are also examined. Finally, a range of factors which can be used as a standard set when examining the QOUL in European cities is proposed.
Keywords: 330